Mapping three-dimensional velocity in a large gravel-bed river - Movafagh Kerman, Soheil (University of Ottawa (Canada), 2007)
Three-dimensional images of the boundary, water surface elevation, and velocity vectors in a wandering gravel-bed reach of Fraser River, British Columbia, are prepared. Data were collected through intensive surveying of a 6 km reach using an Acoustic Doppler Current Profiler (ADCP) and Real Time Kinematic GPS (RTK-GPS) mounted on a boat. Nominal channel width was 500 m, and diagonal sections were spaced an average of 120m apart. Using Matlab, binary data in ADCP raw data files are extracted and converted to ASCII format to be usable by Surfer, Tecplot, and other programs. Measured vertical velocities for each single ping ensemble are corrected for boat motion using simultaneous instantaneous change in GPS rover altitude recorded in the navigation data files. Using Surfer, water surface elevation and bottom boundary elevation are interpolated to 25m x 25m grids and combined together to form the boundary of a volume grid. The ASCII files are reformatted in Excel to produce water surface and channel boundary images in Tecplot. The three-dimensional velocity field is interpolated using kriging, and vorticity is calculated based on the velocity field. The error velocity is calculated as well. The high velocity follows the thalweg and reveals the coherence of the interpolated velocity field and the validity of the method. The three-dimensional velocity field and vorticity are analyzed to assess the cause of high bank erosion and sediment transport observed at a particular location. Erosion at this site appears to be related to complicated flow at a channel confluence and 3D vortices produced by flow separation around a riprap nickpoint.
Keywords: Hydrology.; Engineering, Civil.